Pemberdayaan UMKM Berbasis Digital melalui Pelatihan Literasi Keuangan dan Strategi Pemasaran Online pada Xiyue dalam Meningkatkan Kemandirian Ekonomi Lokal - Nikhlis, Neilin; Huda, Miftahul; Reinnamah, tarla Elviva (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This community service program was motivated by low financial literacy and suboptimal use of digital promotion among culinary MSME actors, resulting in poorly managed cash flow and limited business growth. This topic was selected because strengthening managerial and marketing capacities is essential to improving MSME competitiveness amid increasingly competitive market conditions. The program was implemented through a participatory-applicative approach in the form of simple financial bookkeeping training, cost control assistance, and optimization of social media-based digital promotion. Evaluation was conducted by comparing conditions before and after the program, both in terms of financial literacy understanding and business performance. The results indicated an increase in financial literacy comprehension and an average revenue growth of 12% within one month after the training. In addition, the business owner began applying data-based decision-making and more structured purchasing planning. These findings confirm that contextual training based on partners' real needs is effective in strengthening business capacity and supporting the sustainable economic development of MSMEs.